G657 The experience of using the internet among children and young people with ADHD. (May 2019) - Ayyash, HF; Low, A; Ogundele, MO; Ayyash, FF; Weisblatt, EJL
Abstract : Background: The internet plays an important role in healthcare with both beneficial and detrimental effects. 99% of 12–15 year olds and 94% of 8–11 year olds have access to the internet either in or out of home 1 . Internet use may impact on symptoms and management of ADHD, or be more (or less) prevalent amongst children and young people (CYP) with ADHD than their peers without ADHD, or both. Aims: To evaluate the current evidence for differences in internet use and possible detrimental or beneficial effects on CYP with ADHD. To explore availability of mobile apps on the internet stores which may be helpful in the management of CYP with ADHD in the UK. Methods: A search was performed on Medline, Embase and Psychinfo databases for published articles relating to ADHD and internet use, using relevant search terms. A search was also performed for apps relevant to CYP with ADHD on the 2 most popular mobile platforms in the UK, the Android and Apple systems. Results: A total of 45 articles relevant to internet use and ADHD in CYP were identified. The majority of studies targeted the relationship between internet addiction and ADHD, closely followed by the internet use behaviours of parents and ADHD patients. Less common themes included sleep, behaviour therapy, mobile apps, bullying and safe use of the internet. A total of 245 Android and 102 Apple apps were found. Many of these apps were aimed towards users making a self-diagnosis of ADHD, and a few others aimed at improving ADHD management. A large number of the apps were targeted for adult use and were mostly based on non-existent or poor-quality evidence base, thereby limiting their usefulness among CYP with ADHD. Internet use by CYP with ADHD was found to be almost universal. Most CYP and their parents have never received professional advice about reliable and validated internet resources to use for facilitating the management of ADHD. Conclusions: Internet use may be higher in CYP with ADHD but to date there is no evidence for the direction of causality. There are a large number of online/mobile apps available to health professionals and the public, though the evidence base for these is weak. We have compiled a smaller list of potentially useful apps which may be worthy of further investigation. A questionnaire to assess internet use amongst children with ADHD in our service will be co-produced with CYP with ADHD and parents, with information derived from the literature review as a starting point. Further research is needed in order to develop evidence-based recommendations about user-friendly internet resources which are useful for ADHD patients and their parents and to investigate effects of internet use on ADHD, or vice versa. Reference: Ofcom. UK children's media literacy . April2011.